Facilitating decision-making in women undergoing genetic testing for hereditary breast cancer: BRECONDA randomized controlled trial results. (December 2017) - Sherman, Kerry A.; Kilby, Christopher J.; Shaw, Laura-Kate; Winch, Caleb; Kirk, Judy; Tucker, Kathy; Elder, Elisabeth
Abstract: Background: Decision-making concerning risk-reducing mastectomy for women at hereditary risk of breast cancer entails complex personal choices. Deciding whether and how to restore breast shape after risk-reducing mastectomy is a key part of this process. We developed a web-based decision aid, BRECONDA ( B reast Recon struction D ecision A id), to assist women in decision-making regarding breast reconstruction. Method: This study assessed the efficacy of BRECONDA to assist women at increased risk of breast cancer in making decisions regarding risk-reducing mastectomy in terms of decisional conflict, knowledge, and satisfaction with information. Women at hereditary risk of breast cancer ( N  = 64) were recruited into this randomized controlled trial from four Australian hereditary cancer clinics. Participants initially provided online consent and completed baseline questionnaires assessing decisional conflict, knowledge, and satisfaction with information. They were then randomly assigned to either: 1) Intervention – unlimited access to BRECONDA, with usual care; or, 2) Control – usual care. At 2-months follow-up ( N  = 60) the outcomes were re-assessed. Intervention participants also completed user acceptability ratings for the intervention overall and specific key modules. Results: MANCOVA analyses indicated that Intervention participants reported lower decisional conflict ( P  = 0.027), and greater knowledge ( P  = 0.019) and satisfaction with information ( P  < 0.0005) at 2-months follow-up compared with Controls. Intervention participants reported high user acceptability and satisfaction with the intervention. Conclusion: BRECONDA benefits women considering risk-reducing mastectomy by reducing decisional conflict, and improving knowledge and satisfaction with information. These benefits, coupled with high user acceptability, demonstrate the feasibility of implementing BRECONDA in the hereditary cancer risk context. Highlights: Decisions about mastectomy to reduce genetic risk of breast cancer are complex. This also entails decisions about potential breast reconstruction with mastectomy. This complex decision-making can lead to decisional conflict. We tested the efficacy of the BRECONDA intervention to reduce this conflict. BRECONDA improved decisional conflict, knowledge, and information satisfaction.